A New Class of Fluorinated A2A Adenosine Receptor Agonist with Application to Last‐Step Enzymatic [18F]Fluorination for PET Imaging. (21st September 2017) - Lowe, Phillip T.; Dall'Angelo, Sergio; Mulder‐Krieger, Thea; IJzerman, Adriaan P.; Zanda, Matteo; O'Hagan, David
Abstract: The A2A adenosine receptor belongs to a family of G‐coupled protein receptors that have been subjected to extensive investigation over the last few decades. Due to their prominent role in the biological functions of the heart, lungs, CNS and brain, they have become a target for the treatment of illnesses ranging from cancer immunotherapy to Parkinson's disease. The imaging of such receptors by using positron emission tomography (PET) has also been of interest, potentially providing a valuable tool for analysing and diagnosing various myocardial and neurodegenerative disorders, as well as offering support to drug discovery trials. Reported herein are the design, synthesis and evaluation of two new 5′‐fluorodeoxy‐adenosine (FDA)‐based receptor agonists (FDA‐PP1 and FDA‐PP2), each substituted at the C‐2 position with a terminally functionalised ethynyl unit. The structures enable a synthesis of 18 F‐labelled analogues by direct, last‐step radiosynthesis from chlorinated precursors using the fluorinase enzyme (5′‐fluoro‐5′‐deoxyadenosine synthase), which catalyses a transhalogenation reaction. This delivers a new class of A2A adenosine receptor agonist that can be directly radiolabelled for exploration in PET studies. Abstract : PET idea : The synthesis and evaluation of a new class of A2a adenosine receptor agonist, designed around a 5′‐fluorodeoxy‐adenosine scaffold, are reported. The fluoromethyl group at the C‐5′ position allows for the radiosynthesis of [ 18 F]PET tracer analogues by enzymatic fluorination of chlorinated precursors with [ 18 F]fluoride.